Does a monetary incentive improve the response to a postal questionnaire in a randomised controlled trial? The MINT incentive study. - Gates, S; Williams, M; Withers, E; Williamson, E; Mt-Isa, S; Lamb, S (2009)
BACKGROUND: Sending a monetary incentive with postal questionnaires has been found to improve the proportion of responders, in research in non-healthcare settings. However, there is little research on use of incentives to improve follow-up rates in clinical trials, and existing studies are inconclusive. We conducted a randomised trial among participants in the Managing Injuries of the Neck Trial (MINT) to investigate the effects on the proportion of questionnaires returned and overall non-response of sending a 5 pounds gift voucher with a follow-up questionnaire. METHODS: Participants in MINT were randomised to receive either: (a) a 5 POUNDSgift voucher (incentive group) or (b) no gift voucher (no incentive group), with their 4 month or 8 month follow-up questionnaire. We recorded, for each group, the number of questionnaires returned, the number returned without any chasing from the study office, the overall number of non-responders (after all chasing efforts by the study office), and the costs of following up each group. RESULTS: 2144 participants were randomised, 1070 to the incentive group and 1074 to the no incentive group. The proportion of questionnaires returned (RR 1.10 (95% CI 1.05, 1.16)) and the proportion returned without chasing (RR 1.14 (95% CI 1.05, 1.24) were higher in the incentive group, and the overall non-response rate was lower (RR 0.68 (95% CI 0.53, 0.87)). Adjustment for injury severity and hospital of recruitment to MINT made no difference to these results, and there were no differences in results between the 4-month and 8-month follow up questionnaires. Analysis of costs suggested a cost of 67.29 POUNDS per additional questionnaire returned. CONCLUSION: Monetary incentives may be an effective way to increase the proportion of postal questionnaires returned and minimise loss to follow-up in clinical trials. TRIAL REGISTRATION NUMBER: ISRCTN61305297.